The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2015
DOI: 10.1097/md.0000000000002067
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Analysis of Oral Bacteria in Heart Valve of Patients With Cardiovascular Disease by Real-Time Polymerase Chain Reaction

Abstract: Structural deficiencies and functional abnormalities of heart valves represent an important cause of cardiovascular morbidity and mortality, and a number of diseases, such as aortic stenosis, have been recently associated with infectious agents. This study aimed to analyze oral bacteria in dental plaque, saliva, and cardiac valves of patients with cardiovascular disease. Samples of supragingival plaque, subgingival plaque, saliva, and cardiac valve tissue were collected from 42 patients with heart valve diseas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
42
0
2

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 50 publications
(52 citation statements)
references
References 33 publications
4
42
0
2
Order By: Relevance
“…Dental plaque samples were obtained from the buccal and mesial surfaces of all teeth present using curettes and sterile absorbent paper cones. The samples were stored in a sterile vessel containing phosphate‐buffered saline (PBS) at −20°C for the molecular analysis …”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Dental plaque samples were obtained from the buccal and mesial surfaces of all teeth present using curettes and sterile absorbent paper cones. The samples were stored in a sterile vessel containing phosphate‐buffered saline (PBS) at −20°C for the molecular analysis …”
Section: Methodsmentioning
confidence: 99%
“…Aortic valve leaflets from five corpses submitted to autopsy were obtained aseptically up to 10 hours after death in the Forensic Expertise of the State of Ceará (PEFOCE). One part of the tissue sample was stored in a sterile Eppendorf tube containing PBS at −20°C for real‐time PCR analysis, and the other portion was maintained in 10% buffered formalin for the histological evaluations (hematoxylin and eosin‐HE staining), histochemistry (Giemsa staining), and immunohistochemistry (streptavidin‐biotin‐peroxidase).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Using polymerase chain reaction (PCR), oral bacteria Streptococcus mutans, Prevotella intermedia, Porphyromonas gingivalis, Treponema denticola and Aggregatibacter actinomycetemcomitans have all been detected on cardiac valve samples [5,6]. Antibodies to oral gram-negative (gm−) bacteria have been detected in the synovial fluid of patients with rheumatoid arthritis (RA) and it has been found that patients with RA are more likely to develop periodontitis despite age and smoking history; even further, patients with periodontal infections are less responsive to RA treatments [4].…”
Section: Introductionmentioning
confidence: 99%
“…The incidence of bacteremia and related systemic diseases due to oral anaerobic bacteria following different procedures such as: endodontic treatment, tooth extraction, periodontal surgery, tongue scraping and root scaling has been well documented [10][11][12][13][14][15][16][17][18][19][20][21][22][23][24][25][26][27] and anaerobe periodontal bacteria are isolated more frequently than facultative anaerobic bacteria, such as Streptococcus spp. [28].…”
Section: Oral Surgery and Risk For Bacteremiamentioning
confidence: 99%